Evaluation of test-kits for the detection of Escherichia coli O157 in raw meats and cattle faeces. - Hilda Nyati; Annet Heuvelink; Caroliene Van Heerwaarden; Ans Zwartkruis (International Journal of Food Studies)
Escherichia coli O157 detection limits in artificially contaminated beef and cattle faeces samples were determined using Dynabeads anti E. coli O157 immunomagnetic beads, VIDAS-UP, VIDAS-ICE, and real-time PCR (GeneDisc and LightCycler) systems. Dynabeads anti-E. coli O157 immunomagnetic separation (IMS) and the GeneDisc cycler were the most sensitive methods, and could detect an initial 1 CFU in 25g beef samples after 6h of incubation in modified tryptone soya broth with novobiocin (mTSB+n) or buffered peptone water (BPW). The VIDAS-UP method could detect an initial 10 CFU, while VIDAS-ICE and the LightCycler methods could only detect an initial 100 CFU. Higher detection rates were achieved with 18 hour incubations, where an initial 1 CFU in a 25g sample could be detected with all five methods. For cattle faeces enrichments, Dynabeads anti-E. coli O157 IMS could detect an initial 1 CFU after a 6 h incubation in mTSB+n, while the VIDAS-UP and VIDAS-ICE methods could detect an initial 10 CFU and both PCR methods could only detect an initial 100 CFU. Detection rates were lower in BPW, compared to mTSB+n, with thresholds of 100 CFU for VIDAS-ICE, VIDAS-UP and GeneDisc methods, and >100 CFU for the LightCycler method.